Lignin-containing cellulose nanofibrils improving the papermaking process and the properties of handsheet paper - Mhd Idris, Farah Nabila (2023)
The addition of cellulose nanofibrils (CNF) during papermaking is associated with lower productivity processing due to the increase in drainage time, as the CNF addition contributes to the improved inter-fiber network due to hydrophilic interaction. Additionally, its nano-sized enables it to fill the empty space in between the fibers and eventually slows down the water removal. To overcome this issue, partially hydrophilic CNF was prepared by retaining the lignin content in CNF to produce lignin-containing CNF (LCNF). Four types of LCNF samples namely UB, D1, D2 and D3 with various lignin content of 9.7%, 7.7%, 2.8%, and 0.5%, respectively, were prepared from oil palm empty fruit bunch (OPEFB) by manipulating the pulping condition and introducing controlled bleaching process. The effects of LCNF lignin content and LCNF loading (1, 2, 4 and 8 wt%) on drainage time and handsheet characteristics were evaluated. Unbleached OPEFB base pulp was used as control. Overall results showed that lignin content played a significant role in drainage time, whereby the lower the lignin content, the longer the drainage time. For instance, D3 sample which contained almost no lignin gave the longest drainage time at 35.6 s, compared to control sample (8.0 s). LCNF loading also affected the drainage time with 2 wt% of D1 LCNF sample gave the shortest drainage time among all of the LCNF samples. In terms of the mechanical properties of the handsheet, LCNF incorporation seemed to contribute to better results compared to the control sample. For example, the incorporation of 4 wt% D1 LCNF had a tensile index of 36.9 Nm/g, burst index of 5.4 kPa.m²/g, and folding strength of 152 double folds compared to the control sample which had a tensile index of 31.8 Nm/g, burst index of 4.3 kPa.m²/g, and folding strength of 62 double folds. Overall results showed that the use of LCNF in papermaking shortened the drainage time as compared to CNF which contributed to better paper processing. Additionally, the LCNF exhibited incorporation effects with improved physical and mechanical properties as compared to the control sample.